2004
DOI: 10.5194/acp-4-281-2004
|View full text |Cite
|
Sign up to set email alerts
|

Particle size distribution and particle mass measurements at urban,near-city and rural level in the Copenhagen area and Southern Sweden

Abstract: Abstract. Particle size distribution (size-range 3-900 nm) and PM10 was measured simultaneously at an urban background station in Copenhagen, a near-city background and a rural location during a period in September-November 2002. The study investigates the contribution from urban versus regional sources of particle number and mass concentration.The total particle number (ToN) and NO x are well correlated at the urban and near-city level and show a distinct diurnal variation, indicating the common traffic sourc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
77
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 16 publications
11
77
0
2
Order By: Relevance
“…Figure 6 shows that both distributions were dominated by small, probably nucleation originated particles with a peak size of approximately 20 nm. Similar observation was also reported by Wehner and Wiedensohler (2003) and Ketzel et al (2004). Multimodal lognormal distribution was fitted to the measured distributions to enable the particle density calculation procedure described above.…”
Section: Characteristics Of Road-side Distributionsmentioning
confidence: 79%
See 2 more Smart Citations
“…Figure 6 shows that both distributions were dominated by small, probably nucleation originated particles with a peak size of approximately 20 nm. Similar observation was also reported by Wehner and Wiedensohler (2003) and Ketzel et al (2004). Multimodal lognormal distribution was fitted to the measured distributions to enable the particle density calculation procedure described above.…”
Section: Characteristics Of Road-side Distributionsmentioning
confidence: 79%
“…These values are in good agreement with our study. Ketzel et al (2004) found that the traffic related distributions peaked at 22 nm in the centre of Copenhagen. In addition, Wehner and Wiedensohler (2003) reported the peak in the urban number size distribution around 20 nm.…”
Section: Characteristics Of Road-side Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total particle number measured in urban areas often correlates well with NO x and shows a distinct diurnal variation, indicating a common traffic source (Ketzel et al, 2004;Hussein et al, 2004). Traffic emissions are able to affect submicron particle number concentrations around major roads and may be a dominant source of ultrafine particles (PM 0.1 ) in the urban atmosphere (Despiau and Croci, 2007;Rodriguez et al, 2007).…”
Section: Urban Scalementioning
confidence: 99%
“…Size resolved measurement data reveal that about 90% of these particles have an aerodynamic diameter below 0.5 mm (e.g. Birmili et al, 2009;Ketzel et al, 2004Ketzel et al, , 2007Samaras et al, 2005) and hence are in the health relevant size segment. Vehicle emissions of air pollutants strongly depend on the exhaust emission control devices and their operation efficiency in a given year.…”
Section: Emissions Of Particulate Mattermentioning
confidence: 99%